PEDOT nanocomposites mediated dual-modal photodynamic and photothermal targeted sterilization in both NIR I and II window. (February 2015) - Li, Luoyuan; Liu, Yuxin; Hao, Panlong; Wang, Zhangguo; Fu, Limin; Ma, Zhanfang; Zhou, Jing
Abstract: PEDOT nanoparticles with a suitable nanosize of 17.2 nm, broad adsorption from 700 to 1250 nm, and photothermal conversion efficiency ( η ) of 71.1%, were synthesized using an environmentally friendly hydrothermal method. Due to the electrostatic attraction between indocyanine green (ICG) and PEDOT, the stability of ICG in aqueous solution was effectively improved. The PEDOT nanoparticles modified with glutaraldehyde (GTA) targeted bacteria directly, and MTT experiments demonstrated the low toxicity of PEDOT:ICG@PEG-GTA in different bacteria and cells. Pathogenic bacteria were eﬀectively killed by photodynamic therapy (PDT) and photothermal therapy (PTT) with PEDOT:ICG@PEG-GTA in the presence of near-infrared (NIR) irradiation (808 nm for PDT, and 1064 nm for PTT). The combination of the two different bacteriostatic methods was significantly more effective than PTT or PDT alone. The obtained PEDOT:ICG@PEG-GTA may be used as a novel synergistic agent in combination photodynamic and photothermal therapy to inactivate pathogenic bacteria in both the NIR I and II window.